Pemanfaatan Media Whatsapp dalam Meningkatkan Kompetensi Pedagogik Guru dalam Pelaksanaan Pembelajaran Daring (Online) Melalui Supervisi Akademik di Kelas IV SD Negeri 63/X Nibung Putih - Afniati Afniati (Journal on Education, 2022)
This study focused on Teacher Problems in the Implementation of Online Classes during the Covid 19 Pandemic in Thematic Learning for Class IV students at the State Elementary School 63/X Nibung Putih and efforts to overcome the problems found. The approach used in this study is a qualitative approach. The research method used is a natural object, where researchers go directly to the field to find out what problems are faced by teachers in the implementation of online classes during the COVID-19 pandemic in thematic learning of fourth grade students at SDN 63/X Nibung Putih. The goal is to describe a situation that actually exists. The problems experienced by teachers in implementing online classes during the covid-19 pandemic in thematic learning of fourth grade students at SDN 63/X Nibung Putih were limited facilities and knowledge about technology, making online learning only possible through the WhatsApp application, not all students have smartphones, high internet quotas during the pandemic, unstable internet connections, lack of parental assistance during learning causes students to lack discipline, student complaints about assignments that are piling up. Efforts to overcome teacher problems in implementing online classes during the COVID-19 pandemic in thematic learning of fourth grade students at SDN 63/X Nibung Putih, namely providing assistance funds from BOS in accordance with government recommendations for purchasing internet quotas, parents must allocate availability of time to accompany children during learning, teachers can come to students' homes from time to time to provide teaching materials to students or contact students' parents directly to give assignments, teachers do not have to give a lot of assignments to students so they don't feel burdened remembering assignments are not from only one subject.